2022
DOI: 10.1002/nop2.1291
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of simulated video on test anxiety in objective structured clinical examination among nursing and midwifery students: A quasi‐experimental study

Abstract: Clinical education for nursing and midwifery students is more important than theoretical knowledge in developing their clinical competencies. They will soon provide care to people struggling with many different issues (Zamanzadeh et al., 2021). The common method for developing clinical competencies is a clinical simulation where students engage in an artificial situation related to a clinical environment. Some advantages of this method include creating an atmosphere similar to real-life conditions and providin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…The fact that showing a video in the OSCE format does not have an impact on subsequent performance in the OSCE has also been demonstrated by others. A 15-minute video intended to increase familiarity with the exam format decreased stress levels in nursing students but was not accompanied by an increase in OSCE scores (7). An intriguing explanation for this nding is provided by Deslaurier et al They concluded that by mere passive absorption of information but not taking part in the activity, the students felt overcon dent and did not prepare themselves su ciently for the actual OSCE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that showing a video in the OSCE format does not have an impact on subsequent performance in the OSCE has also been demonstrated by others. A 15-minute video intended to increase familiarity with the exam format decreased stress levels in nursing students but was not accompanied by an increase in OSCE scores (7). An intriguing explanation for this nding is provided by Deslaurier et al They concluded that by mere passive absorption of information but not taking part in the activity, the students felt overcon dent and did not prepare themselves su ciently for the actual OSCE.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore unclear how much familiarization with the OSCE format is needed to make it work. Indeed, it has been shown that increasing familiarity with a test by showing a 15-minute OSCE simulation video or implementing a mock OSCE decreases stress levels (7,8). However, controversial data exist regarding whether increasing familiarity has an impact on students´ performance (9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…This fragmented care may negatively affect the pregnancy outcomes and increase the rate of cesarean section [ 18 ]. Furthermore, the results of some studies in Iran indicate that the clinical competence obtained by midwifery students is far from optimal and that they do not acquire the necessary skills and abilities at the end of their studies [ 19 ]. Farrokhi et al showed that the performance quality of 70% of midwives is average, and only 18.5% of them have good quality performance [ 20 ].…”
Section: Introductionmentioning
confidence: 99%